Effectiveness of the Implementation of Pokmas Lipas in Supporting the Social Reintegration of Correctional Clients of Bapas Class II Purwokerto - Ellesse, Karinna; Nugroho, Hibnu; Budiyono, Budiyono (Jurnal Idea Hukum, 2024)
Corrections are organized in an integrated manner between the supervisor, supervised, and community. Recognizing the important role of the community in supporting the social reintegration of correctional clients, the Ministry of Law and Human Rights of the Republic of Indonesia issued the Decree of the Director General of Corrections Number: PAS-06.OT.02.02 2020 dated February 10, 2020, concerning the Guidelines for the Establishment of Pokmas Lipas at Bapas, which will become a partner and forum for community empowerment. The results showed that the effectiveness of the implementation of Pokmas Lipas in supporting the social reintegration of correctional clients of Bapas Class II Purwokerto has not been effective by looking at data on the number of active Pokmas Lipas and the number of clients who follow Pokmas Lipas is very small compared to the total number of clients of Bapas Class II Purwokerto. The obstacles faced are that there is no further regulation on the guidelines for the working mechanism of Pokmas Lipas, the number of Community Supervisors is not proportional to the number of clients and the coverage of a very large work area, and there is still a negative stigma from the community towards clients. Suggestions that can be given are that it is necessary to immediately form a Regulation of the Minister of Law and Human Rights of the Republic of Indonesia concerning guidelines for the work mechanism of Pokmas Lipas, so that there are clear procedures in its implementation and increase the role of Community Supervisors in empowering Pokmas Lipas according to their respective levels.